Pengaruh Kompetensi, Employee Agility, dan Lingkungan Kerja Terhadap Kinerja Karyawan UMKM Mieyabe Noodle & Dimsum - Galih Noer Wahyuni; Rini Armin; Kasnowo Kasnowo (Indo Publishing, 2026)
To remain competitive in current market conditions, employee performancein addition to product quality is a key determinant of business sustainability. MSME employees need adequate competencies, agility in responding to changes in market demand, and a conducive work environment. This study analyzes the influence of competencies, employee agility, and the work environment on employee performance. A quantitative approach using an associative method was employed in this research. The saturated sample included all 35 MSME employees. The researcher collected data through a questionnaire using a Likert scale, and multiple regression analysis was used as the analytical technique. The results show that competence has a significant effect on employee performance (t = 3.861; sig. = 0.001). Employee agility has a significant effect (t = 4.743; sig. = 0.000). The work environment also has a significant effect (t = 3.353; sig. = 0.000). Collectively, these three variables had a significant effect on employee performance (F = 49.716; sig. = 0.000), with a coefficient of determination (R²) of 0.828; these three variables explain 82.8% of the variation in employee performance.